Pengembangan Media Pembelajaran Berbasis Simulator Digital Menggunakan Smart Apps Creator (SAC) pada Mata Pelajaran Penerapan Rangkaian Elektronika (PRE) di SMKN 1 Padang - Shawfani, Aditya (Jurnal Teknik Komputer dan Informatika, 2024)
This research aims to develop Digital Simulator-based learning media using Smart Apps Creator (SAC) in the Application of Electronic Circuits (PRE) subject at SMKN 1 Padang and to determine the level of validity and practicality of the learning media that has been created. This learning media was developed using the Define, Design, Development, Disseminate (4D Model) research model. This learning media will be tested for validity and practicality testing (user trials). Validity testing was carried out by material experts and media experts. The practicality test was carried out by a small group of twenty students. The validity test results obtained were 0.975 from media expert validators which were categorized as "Valid" and 0.917 from material expert validators which were categorized as "Valid". The results of the practicality test carried out on students, obtained an average rating of 85,2% which was categorized as "Very Practical". Based on the results of research and development of Digital Simulator-based learning media in Electronic Circuit Application (PRE) subjects with valid and very practical categories for use.